Intravitreal anti-vascular endothelial growth factor injection combined with panretinal photocoagulation for neovascular glaucoma in Indonesian patients with diabetes mellitus: a prospective study (Medical Journal of Indonesia, 2019)
BACKGROUND The aim of this study was to determine the levels of vascular endothelial growth factor (VEGF) in the aqueous humor and the effect of intravitreal anti-VEGF injection combined with panretinal photocoagulation (PRP) on the management in diabetes mellitus (DM) patients with neovascular glaucoma (NVG). METHODS This study was a prospective, interventional study in DM patients with NVG. Paracentesis followed by intravitreal bevacizumab (IVB) injection was performed in all eyes. The concentration of VEGF obtained from paracentesis was measured. In week-1, the intraocular pressure (IOP), sectorial iris neovascularization (NVI), and visual acuity were documented, and management was continued with PRP laser over a period of 1 week. All parameters and additional interventions performed after PRP were also recorded. RESULTS A total of 18 eyes from 17 patients were studied. The mean (SD) level of VEGF in the aqueous humor was 3,864 (1,468) pg/ml, and the mean (SD) of initial IOP was 39 (10.2) mmHg. There was a significant reduction in IOP in week-1 after the first intervention to 24.4 (8.0) mmHg (p = 0.001); however, at 2 weeks the IOP increased to 30.4 (6.7) mmHg. NVI showed significant regression in week-1 after IVB combined with PRP laser (p < 0.05). All eyes required additional glaucoma implants (14 eyes) and cyclocryotheraphy (4 eyes). CONCLUSIONS In the eyes of diabetes patients with NVG, VEGF levels were high. With the use of IVB, the IOP was reduced, and NVI regressed; however, due to the severe stages of disease, all eyes required glaucoma surgery.